Histopathological assessment of intrinsic laryngeal musculature in horses with dynamic laryngeal collapse. (13th November 2014) - Fjordbakk, C. T.; Revold, T.; Goodwin, D.; Piercy, R. J.
Summary Reasons for performing study The pathogenesis of bilateral dynamic laryngeal collapse associated with poll flexion (DLC) of horses is unknown but might be associated with intrinsic laryngeal muscle weakness. Objectives To investigate histopathological characteristics of the cricoarytenoideus dorsalis, the cricothyroid (CT) and the cricoarytenoideus lateralis muscles in DLC‐affected horses and compare these with unaffected controls. Our hypotheses were that evidence of neurogenic atrophy of the CT or cricoarytenoideus dorsalis muscles would be found in DLC‐affected horses and that observed changes would be symmetrically (left/right) distributed, or that muscle fibre diameter would be significantly reduced in DLC‐affected horses compared to unaffected controls, reflecting an underlying paresis. Study design Case–control study. Methods Five DLC horses and 8 controls were included. Muscle samples were harvested immediately following euthanasia. Fibre type proportions and size were evaluated by multiple immunofluorescence labelling of cryosections, and compared between sides (left/right) and groups (DLC‐affected cases/ unaffected controls). Subjective and objective assessments of fibre type grouping were compared between sides and groups. Results Fibre type proportions, fibre size and the subjective assessment of fibre type grouping did not reveal any statistically significant differences between the groups. Objective assessment of fibre type grouping revealed significantly more large clusters of T1 fibres within the left cricoarytenoideus lateralis muscle of DLC‐affected cases versus controls, and within the right CT muscle of control horses compared to the DLC‐cases. Conclusions The absence of bilateral symmetric fibre type grouping, fibre type loss and fibre atrophy in the DLC‐affected cases do not support a neuromuscular component within the pathogenesis of DLC. The objective assessment of fibre type grouping revealed some statistical differences between the DLC‐affected cases and the unaffected controls; however, these findings were inconsistent with regard to DLC. An alternative aetiology of DLC seems likely.